2021
DOI: 10.1136/bmjopen-2020-046796
|View full text |Cite
|
Sign up to set email alerts
|

Measuring research capacity development in healthcare workers: a systematic review

Abstract: ObjectivesA key barrier in supporting health research capacity development (HRCD) is the lack of empirical measurement of competencies to assess skills and identify gaps in research activities. An effective tool to measure HRCD in healthcare workers would help inform teams to undertake more locally led research. The objective of this systematic review is to identify tools measuring healthcare workers’ individual capacities to conduct research.DesignSystematic review and narrative synthesis using Preferred Repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
(66 reference statements)
0
6
0
Order By: Relevance
“…The questionnaire’s closed questions (Figures 8 to 20) were designed to address the objectives of the study. Despite that, several tools to measure research capability have been developed, a ‘globally applicable comprehensive tools to provide comparable, standardised and consistent measurements of research competencies’ has not been found (Bilardi et al 2021: p1 ). Luckson et al (2018) developed several themes from exploring the research culture of nurses and AHPS in the United Kingdom around barriers, enablers and motivators for research.…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire’s closed questions (Figures 8 to 20) were designed to address the objectives of the study. Despite that, several tools to measure research capability have been developed, a ‘globally applicable comprehensive tools to provide comparable, standardised and consistent measurements of research competencies’ has not been found (Bilardi et al 2021: p1 ). Luckson et al (2018) developed several themes from exploring the research culture of nurses and AHPS in the United Kingdom around barriers, enablers and motivators for research.…”
Section: Methodsmentioning
confidence: 99%
“…The validated Research Capacity and Culture (RCC) questionnaire [21] was selected as the best available tool to comprehensively measure perceptions of research capacity and culture through self-reported ratings of research success/skill across a range of individual, team-and organisation-level research constructs [23]. Previously published studies using the RCC tool in the UK have targeted relatively small samples of AHPs from a single healthcare organisation [24][25][26].…”
Section: Methodsmentioning
confidence: 99%
“…Comer et al are unique amongst these studies in concluding individual and organisational research success and/or skill level to be adequate. The absence of evidence and objective measures to determine an adequate skill and success level in AHP research capacity arguably enables this outlying interpretation [ 15 ]. Until progress is made in this respect, it is important that findings from all studies in this field are considered and serve as a proxy indicator of the current status to ensure that individual AHPs and the organisations in which they work are not overlooked in future RCB strategies.…”
Section: Main Textmentioning
confidence: 99%